Catholic Social Teaching and the economy: How to approach “New Things” today? - Sugranyes Bickel, Domingo (Razón y fe, 2020)
When it comes to economic issues, the Catholic Magisterium treads on controversial ground. It did so for the first time in 1891 with Rerum novarum after a long preparation in European Catholic circles and gained a notable influence in the creation of institutions. In the face of today’s profound changes, can the Magisterium speak of economy for all? Is it possible that in the Church today a message is formulated that is as effective as that of 129 years ago?
Keywords: business ethics; Christian social thought; Church history